How to win friends and influence people - Carnege, Dale. (New York Simon and Schuster, 1936)
For 75 years, the rock-solid, time-tested advice in Dale Carnegie's How to Win Friends and Influence People has carried thousands of now-famous people up the ladder of success in their business and personal lives.
Keywords: Leadership